Why are Some Countries so Poor? Another Look at the Evidence and a Message of Hope - Cohen, Daniel (OECD Publishing, 2002)
The paper attempts to explain why single factor explanations of the poverty of nations are usually found to be unsatisfactory. Middle- and low-income countries excluding sub-Saharan Africa, for instance, have an income per head which stands at about one third of the rich countries' income per head. Yet each of the three items of the Solow model, namely human capital, physical capital (appropriated weighted) and total factor productivity, are each equal to about 70 per cent of the corresponding levels of rich countries. But 70 per cent to the power of three is 35 per cent! Multiplying small or relatively benign handicaps can yield dramatic effects on a country's income. The paper then moves on to explain each of the three items. It argues that the Lucas paradox on why capital is scarce can readily be solved, once market prices rather than PPP prices are used to assess the return to capital mobility, and on the same ground it argues that PPP calculations bias downwards the TFP of ...
Keywords: Development